2009
DOI: 10.1111/j.1750-3841.2009.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chemical and Sensory Properties of Migaki‐Nishin (Dried Herring Fillet) during Drying

Abstract: ABSTRACT:Migaki-nishin is a Japanese term that refers to dried herring fillets. It is widely consumed in Japan due to its characteristic flavor enhancing properties. This study was conducted to investigate the changes in chemical and sensory properties of migaki-nishin during drying. Chemical analyses showed that extractive nitrogen and amount of peptides increased significantly (P < 0.05) up to the eighth day of drying and then slightly decreased by the tenth day. Glutamic acid, alanine, glycine, and histidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Lipolysis releases DHA which contributes to the characteristic taste and flavor of dried herring fillet (Shah et al, 2009b). In another study, it was also observed that non-enzymatic browning reactions occur in herring fillet during the drying period (Shah et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lipolysis releases DHA which contributes to the characteristic taste and flavor of dried herring fillet (Shah et al, 2009b). In another study, it was also observed that non-enzymatic browning reactions occur in herring fillet during the drying period (Shah et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Lipolysis releases DHA which contributes to the characteristic taste and flavor of dried herring fillet (Shah et al, 2009b). In another study, it was also observed that non-enzymatic browning reactions occur in herring fillet during the drying period (Shah et al, 2009a).Creatine and creatinine have been reported as taste active components in many foods such as beef (Snider and Baldwin, 1981;Schlichtherle-Cerny and Grosch, 1998;Cambero et al, 2000), lamb and pork (Macy et al, 1970), Vietnamese fish sauce (Park et al, 2002) and dried skipjack (Fuke and Konosu, 1991). In a previous study, we found that creatine and creatinine enhanced the characteristic flavor of thickness, mouthfulness and continuity when added to the Japanese noodle soup (Shah et al, 2010).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Japanese noodle soup was prepared according to the method described by Shah et al (2009), diluted with six volumes of distilled water and used as the control solution.…”
Section: Sensory Evaluationmentioning
confidence: 99%